Use of the Pain Assessment Screening Tool and Outcomes Registry in an Army Interdisciplinary Pain Management Center, Lessons Learned and Future Implications of a 10-Month Beta Test. (1st March 2017) - Flynn, Diane M.; Cook, Karon; Kallen, Michael; Buckenmaier, Chester; Weickum, Ricke; Collins, Teresa; Johnson, Ashley; Morgan, Dawn; Galloway, Kevin; Joltes, Kristin
ABSTRACT: Introduction: The U.S. Army Comprehensive Pain Management Campaign Plan was launched in 2010 to improve pain outcomes in military populations. Interdisciplinary Pain Management Centers (IPMCs) were established at every Army medical center, each offering a robust array of treatment options including conventional and complementary and integrative medicine (CIM) pain management therapies. The Pain Assessment Screening Tool and Outcomes Registry (PASTOR) was developed to assess and track biopsychosocial aspects of pain management and to identify best treatment practices. Methods: During a 10-month pilot test of PASTOR at one Army IPMC, active duty patients completed PASTOR at baseline and at significant junctures during their therapeutic course. Results: 322 IPMC patients completed baseline and follow-up PASTOR assessments. The PASTOR outcomes were analyzed for patients who completed a 3- to 6-week CIM program, a 3-week functional restoration program, or both. For most PASTOR domains, a greater proportion of patients who completed both programs reported important improvement compared with patients who completed either program alone. Conclusions: This pilot test demonstrated the utility of using PASTOR in a military IPMC to track biopsychosocial treatment outcomes. These preliminary data will inform future comparative effectiveness analyses of pain therapies among military and veteran populations.